Production of butyric acid from acid hydrolysate of corn husk in fermentation by Clostridium tyrobutyricum: kinetics and process economic analysis - Xiao, Zhiping (Biotechnol Biofuels, 2018)
BACKGROUND: Butyric acid is an important chemical currently produced from petrochemical feedstocks. Its production from renewable, low-cost biomass in fermentation has attracted large attention in recent years. In this study, the feasibility of corn husk, an abundant agricultural residue, for butyric acid production by using Clostridium tyrobutyricum immobilized in a fibrous bed bioreactor (FBB) was evaluated. RESULTS: Hydrolysis of corn husk (10% solid loading) with 0.4 M H(2)SO(4) at 110 °C for 6 h resulted in a hydrolysate containing ~ 50 g/L total reducing sugars (glucose:xylose = 1.3:1.0). The hydrolysate was used for butyric acid fermentation by C. tyrobutyricum in a FBB, which gave 42.6 and 53.0% higher butyric acid production from glucose and xylose, respectively, compared to free-cell fermentations. Fermentation with glucose and xylose mixture (1:1) produced 50.37 ± 0.04 g L(−1) butyric acid with a yield of 0.38 ± 0.02 g g(−1) and productivity of 0.34 ± 0.03 g L(−1) h(−1). Batch fermentation with corn husk hydrolysate produced 21.80 g L(−1) butyric acid with a yield of 0.39 g g(−1), comparable to those from glucose. Repeated-batch fermentations consistently produced 20.75 ± 0.65 g L(−1) butyric acid with an average yield of 0.39 ± 0.02 g g(−1) in three consecutive batches. An extractive fermentation process can be used to produce, separate, and concentrate butyric acid to > 30% (w/v) sodium butyrate at an economically attractive cost for application as an animal feed supplement. CONCLUSION: A high concentration of total reducing sugars at ~ 50% (w/w) yield was obtained from corn husk after acid hydrolysis. Stable butyric acid production from corn husk hydrolysate was achieved in repeated-batch fermentation with C. tyrobutyricum immobilized in a FBB, demonstrating that corn husk can be used as an economical substrate for butyric acid production.